17β-Estradiol up-regulates Nrf2 via PI3K/AKT and estrogen receptor signaling pathways to suppress light-induced degeneration in rat retina. (24th September 2015) - Zhu, C.; Wang, S.; Wang, B.; Du, F.; Hu, C.; Li, H.; Feng, Y.; Zhu, R.; Mo, M.; Cao, Y.; Li, A.; Yu, X.
Graphical abstract: Highlights: βE2 reduces ROS production in a light-induced rat model of retinal degeneration. βE2 administration up-regulates NRF2 expression. βE2 regulates NRF2 via two pathways: a nongenomic PI3K/AKT response and a genomic ER response. Abstract: Human age-related retinal diseases, such as age-related macular degeneration (AMD), are intimately associated with decreased tissue oxygenation and hypoxia. Different antioxidants have been investigated to reverse AMD. In the present study, we describe the antioxidant 17β-estradiol (βE2) and investigate its protective effects on retinal neurons. Fourteen days after ovariectomy, adult Sprague–Dawley rats were exposed to 8000-lux light for 12 h to induce retinal degeneration. Reactive oxygen species (ROS) levels were assessed by confocal fluorescence microscopy using 2, 7-dichlorofluorescein diacetate. Nuclear factor erythroid 2-related factor 2 ( Nrf2 ) and antioxidant enzyme mRNA expression were detected by real-time PCR. Western blotting was used to evaluate NRF2 activation. NRF2 translocation was determined by immunohistochemistry, with morphological changes monitored by hematoxylin and eosin staining. Following light exposure, βE2 significantly reduced ROS production. βE2 also up-regulated NRF2 mRNA and protein levels, with maximal expression at 4 and 12 h post-exposure, respectively. Interestingly, following βE2 administration, NRF2 was translocated from the cytoplasm to the nucleus, primarily in the outer nuclear layer. βE2 also up-regulated NRF2, which triggered phase-2 antioxidant enzyme expression (superoxide dismutases 1 and 2, catalase, glutaredoxins 1 and 2, and thioredoxins 1 and 2), reduced ROS production, and ameliorated retinal damage. However, the beneficial effects of βE2 were markedly suppressed by pretreatment with LY294002 or ICI182780, specific inhibitors of the phosphatidylinositol 3-kinase–Akt (PI3K/AKT), and estrogen receptor (ER) signaling pathways, respectively. Taken together, these observations suggest that βE2 exerts antioxidative effects following light-induced retinal degeneration potentially via NRF2 activation. This protective mechanism may depend on two pathways: a rapid, non-genomic-type PI3K/AKT response, and a genomic-type ER-dependent response. Our data provide evidence that βE2 is a potentially effective in the treatment of retinal degeneration diseases.